IMPLEMENTASI KERJASAMA INDONESIA-KOREA SELATAN DALAM PENEMPATAN DAN PERLINDUNGAN PEKERJA MIGRAN TAHUN 2015-2018 - Yuniarti Lestari Putri Br Purba (2023)
This study aims to find out how Indonesia and South Korea cooperate in placement related to the protection of migrant workers and to find out the role of BP2MI and MOEL in implementing the social security program for migrant workers using the theory of Bilateral Cooperation, International Migration and Foreign Policy Implementation theory. The method used is descriptive qualitative using primary and secondary data. Data collection techniques were carried out by interviews and literature studies. The author uses four stages of data analysis according to Miles, namely data collection, data reduction, data presentation, and drawing conclusions/data verification.The final results of this study indicate that the Indonesian government has actively collaborated with South Korea in placing PMI regarding the protection of migrant workers through social security programs. The factors underlying PMI's migration to South Korea are based on an even distribution of population growth and salary considerations between countries of origin with a minimum of high school graduates. Adequate numbers of high school graduates have not been absorbed due to the decision of the selected candidates based on the authority of the employer company. This is evident because the company has not been able to recruit many workers because the costs incurred by PMI during the placement process are borne by the employer.